ANALISIS PENGARUH INFLASI, BI RATE, GIRO WAJIB MINIMUM DAN NON PERFORMING LOANS TERHADAP PERTUMBUHAN KREDIT - MUHAMMAD IBRA RACHMANSYAH (2021)
Monetary policy mix is one of the most frequently used policy in current modern economy. Dictating the flow of credit and money are keys to an proper economic stability. Indonesia's credit growth over the last 10 years tends to continue to decline and does not meet the target, indicating a ineffective monetary policy mix. This study aims to determine the effect of Inflation, BI Rate, Reserves Requirements and Non-Performing Loans. The data is in the form of time series and is secondary data obtained from Bank Indonesia, the Central Statistics Agency and the Financial Services Authority from 2009 to 2019 with total sample of 40. This study uses multiple linear regression techniques and the tools used to analyze this research are Eviews 10 with a significance level of 5% (0.05). The results of the study partially show that (1) inflation has a significant effect on credit growth (2) the BI Rate has no effect on credit growth (3) Reserves requirements has a significant effect on credit growth (4) Non-Performing Loans has a significant effect on credit growth.